Condensed Tannins from the bark of Guazuma ulmifolia Lam. (Sterculiaceae) - Lopes,Gisely C. (2009)
From the bark of Guazuma ulmifolia Lam. (Sterculiaceae), nine compounds were isolated and identified: ent-catechin, epicatechin, ent-gallocatechin, epigallocatechin, epiafzelechin-(4β→8)-epicatechin, epicatechin-(4β→8)-catechin (procyanidin B1), epicatechin-(4β→8)-epicatechin (procyanidin B2), epicatechin-(4β→8)-epigallocatechin, and the new compound 4'-O-methyl-epiafzelechin. Their structures were elucidated on the basis of spectral and literature data. HPLC fingerprint analysis of the semipurified extract was performed on a C18 column, with a mixture of acetonitrile (0.05% trifluoroacetic acid):water (0.05% trifluoroacetic acid) (v/v) with a flow rate of 0.8 mL min-1. The sample injection volume was 100 µL and the wavelength was 210 nm.